2022
DOI: 10.1177/11779322221079232
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Approach to Identify Significant Biomarkers, Drug Targets Shared Between Parkinson’s Disease and Bipolar Disorder: A Pilot Study

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder responsible for shaking, rigidity, and trouble in walking and patients’ coordination ability and physical stability deteriorate day by day. Bipolar disorder (BD) is a psychiatric disorder which is the reason behind extreme shiftiness in mood, and frequent mood inversion may reach too high called mania. People with BD have a greater chance of developing PD during the follow-up period. A lot of work has been done to understand the key factors for developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…A meta-analysis of the PD public dataset showed that SPI1 is the TF of the hub gene (53). Meanwhile, SPI1 is also an important TF of the hub gene in PD with bipolar disorder (54). Besides, a study has demonstrated that SPI1 is a key gene associated with postpartum depression (PPD)(55).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of the PD public dataset showed that SPI1 is the TF of the hub gene (53). Meanwhile, SPI1 is also an important TF of the hub gene in PD with bipolar disorder (54). Besides, a study has demonstrated that SPI1 is a key gene associated with postpartum depression (PPD)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the study revealed an overlap between central and peripheral transcriptomic signatures in PD that are characterized by anomalies in exocytosis and specific genes related to the SNARE complex including vesicle-associated membrane protein 2 ( VAMP2 ), syntaxin 1A ( STX1A ), and p21-activated kinase 1 ( PAK1 ) [ 61 ]. In a separate PD study making use of RNA-seq datasets from the GEO database, several genes including RPL21 , RPL34 , CKS2 , B2M , TNFRSF10A , DTX2 , and HLA-B , have been shown to be upregulated in PD brain tissues [ 62 ]. In MS, a data mining study analyzing RNA-seq datasets from the GEO database has reported that inactive MS brain lesions contain significantly more M2 macrophages compared to normal white matter controls [ 63 ].…”
Section: Omics Spectrum-based Data Mining In Translational Neurosciencementioning
confidence: 99%
“…Many people diagnosed with bipolar disorder have rapid mood swings among other clinical symptomology. Bipolar disorder is categorized into bipolar disorder I and bipolar II which involves recurrent episodes of depressive and manic symptoms [42][43][44]. A diagnosis of bipolar disorder is controversial and some people with bipolar disorder are originally misdiagnosed or underdiagnosed [7,45].…”
Section: Nutrition and Bipolar Disordermentioning
confidence: 99%